Triple diagnostic test in the evaluation of thyroid nodules - Kamini, Snigdha; Arora, Jainendra K.; Jain, Sunil Kumar (International Surgery Journal, 2021)
Background: Thyroid nodules are a common endocrine disease whose prevalence in India is approximately 12.2%. Although most patients with suspected nodules have benign conditions, the overestimation of malignancy leads to the performance of unnecessary procedures. No clinical, radiological and cytological parameters has singularly shown significant impact on clinical practice and post-operative histopathological examination remains the gold standard in the diagnosis of malignancy. Methods: 55 patients with thyroid nodules were evaluated and the Clinical assessment findings were recorded by McGill thyroid nodule score, ultrasonography findings using TIRADS and FNAC findings by the Bethesda system. The triple test was then used to classify them and these results were compared with the HPE of the post-operative specimen. Results: The sensitivity and specificity of TIRADS, FNAC were higher as compared to clinical score; clinical score had lowest sensitivity of 72.73%. The sensitivity, specificity, PPV, NPV and accuracy of triple test was 100%. Triple test had higher sensitivity, specificity and accuracy in differentiating thyroid nodules as compared to any of the three parameters used individually. Conclusions: Triple test has higher accuracy, sensitivity and specificity in determining the nature of thyroid nodule than each of the parameters used individually and it is especially useful in follicular lesions. On the basis of the results of this study, we conclude that the triple test can reliably be used to differentiate benign and malignant nodules preoperatively.